Analysis Error Speaking Indonesian in Student WhatsApp Conversations : PUEBI-based Peer Review Analysis - Andika Herlangga; Saskia Auliani Yansah; Nindy Amanda; Nia Rahmaida Nasution; Nurul Azizah (International Journal of Technology and Education Research, 2026)
communication technology through applications message instant like WhatsApp has change student social interaction patterns. However, this convenience has an impact negative on neglect rules standard Indonesian in order to catch up efficiency communication, which if allowed to interfere with their ability to write scientific papers. Most previous research has focused only on the classification errors descriptively without offering solution practical in space class. This study aims to identify variety error speak Indonesian in WhatsApp conversations with students at the same time test the effectiveness of the peer review learning method based on PUEBI/EYD as an action corrective-collaborative. This research uses a descriptive method qualitative with techniques data collection in the form of studies library, documentation catch screen digital conversations, as well as analysis content analysis of error forms linguistics. Found various deviation massive at the level orthography (abbreviation extreme and modification slang), phonology (deletion phonemes), morphology (confusion writing affixation passive and clitic), as well as syntax (interference regional dialect). Negligence factor psychology and memory formation muscle (muscle memory) from activity type repetitive informal messages proven lower quality accuracy diction student academic performance. Implementation of guideline -based peer review methods spelling standard significantly proven capable cut off cycle habit bad The process of assessing and editing draft conversation colleagues succeed stimulate self -reflection, improving skills editing, and grow return students' cognitive awareness to order speaking standard in the formal academic realm